Green Energies and Public Control: Environmental Concern and Business Ethics - Antúnez Sánchez, Alcides (Mercados y Negocios, 2021)
The article aims to characterize the environmental audit in the different scenarios executed by the audit team of the General Comptroller’s Office in the studied stages of public control in Cuba until the XXI century, it concludes with the public control of green energies by the forms of management that they implement to mitigate pollution and achieve sustainable development by modifying the energy matrix in relation to the Millennium Goals for 2030, indicated by ECLAC.